Effectiveness of an Education Program on Nurses- Midwives’ knowledge toward Postpartum Hemorrhage at Delivery Room of Maternity Hospitals in Baghdad City - ali, azhar; Bahaaldeen, Ezedeen (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: To find out the effectiveness of education program application on nurses-midwives’ knowledge toward prevention and management of postpartum hemorrhage in delivery room and some socio demographic characteristics Methodology: a quasi -experimental "test-retest"design has carried throughout the present study with the application of a pre –test and post- test for nurses-midwives’ knowledge toward postpartum hemorrhage. The study was conducted in six hospitals in Baghdad: Fatima Al – Zahra for Maternity and Pediatric, Al -Elwia maternity, Baghdad Teaching, AL-Imamine Al - Kadhimin Teaching, Al-Karckh maternity and Al-Yarmouk Teaching hospital for the period from 27th May 2018 to10th December 2018. The sample was conducted on Non-probability (purposive sample) of (97)nurse-midwife. Who were evaluated by using as questionnaire for the nurses-midwives’ knowledge which consisted of two parts; the first part included the socio-demographic characteristics of the nurses and the second part included The knowledge of nurses - midwives towards prevention and management of postpartum hemorrhage consists of 43 questions in the form of multiple choices. Descriptive statistical and inferential analyses were used to analyze the data . Results: The result indicates that nurses - midwives’ knowledge and practices about prevention and management of PPH have been greatly improved after their being exposed to the education program. Recommendation: The necessity of making periodical training program must conduct regularly in all obstetric hospitals for all nurses and midwives in the delivery rooms, operating theaters, maternity and maternity and emergency obstetric wards, and it should be mandatory.